The Principal’s Transformational Leadership in Enhancing Teacher Performance in the Digital Era - Yayuk Unsurni (Agrapana Media, 2025)
This study is motivated by the challenges faced by Islamic educational institutions in the digital era, where teachers are required to adapt to technological developments without neglecting spiritual values in the learning process. The main problem identified is the low performance of teachers in utilizing educational technology and developing innovative learning, partly influenced by the lack of visionary and transformational leadership at the principal level. This study aims to analyze how the transformational leadership of the school principal can improve teacher performance at MI Fattahul Huda Pungpungan. The research employs a qualitative approach with a field research design, using in-depth interviews, direct observation, and document analysis. The findings show that the principal applies four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Through the application of these values, the principal is able to build motivation, enhance professionalism, and encourage teachers to innovate in digital-based learning. Furthermore, the religious and moral values instilled by the principal reinforce teachers’ integrity and work ethic. The implications of this study emphasize that transformational leadership grounded in Islamic values is not only relevant for addressing the challenges of the digital era but also effective in creating a collaborative, innovative, and integrity-driven work culture within Islamic educational settings.